1984
DOI: 10.1136/thx.39.7.529
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory responses of diabetics to hypoxia, hypercapnia, and exercise.

Abstract: The respiratory responses of 52 diabetics and 65 non-diabetic controls to hypoxia, hypercapnia, and exercise were studied. Twenty five per cent of the diabetics had evidence of impaired sensitivity to hypoxia or decreased ventilatory response to hypercapnia, while 7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 24 publications
3
43
0
1
Order By: Relevance
“…There is evidence that carotid body function is impaired in diabetic patients. This is suggested by data that show the ventilatory response to hypoxia, which is mediated by the carotid bodies, is diminished in diabetic patients (35)(36)(37)(38). Impaired carotid body function may result from the increased carotid artery wall intima-media thickness that often accompanies glucose-intolerant or insulin-resistant states (39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence that carotid body function is impaired in diabetic patients. This is suggested by data that show the ventilatory response to hypoxia, which is mediated by the carotid bodies, is diminished in diabetic patients (35)(36)(37)(38). Impaired carotid body function may result from the increased carotid artery wall intima-media thickness that often accompanies glucose-intolerant or insulin-resistant states (39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that the HPA axis response to this challenge remains intact in diabetic subjects and is independent of peripheral autonomic dysfunction. However, it should be noted that subjects in the present study were matched in terms of glycaemic control and all had relatively normal glucose levels at the time of testing, and previous studies have reported that uncontrolled diabetes and acute hyperglycaemia or hypoglycaemia may be associated with altered HPA axis activity [12,23]. Cortisol responses to graded exercise have been shown to be impaired in diabetic subjects with autonomic neuropathy, albeit only at maximum workload [14,24], and it has been suggested that this is due to an impairment in sympathetic afferent impulses [24].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models with chemically induced diabetes suggest that abnormal ventilatory responses to hypoxia and/or hypercapnia may be partially responsible (195;196). Studies in diabetic patients also show that abnormalities in O 2 ad CO 2 sensitivity may have an important role in increasing respiratory control instability during sleep (197)(198)(199)(200)(201). Whether diabetes also contributes to mechanical alterations in the upper airway and thus increasing upper airway collapsibility during sleep remains an open question.…”
Section: Diabetes As a Risk Factor For Sleep Apneamentioning
confidence: 99%